From King Lear to King James: The Problem of Ocularcentrism in Early Modern England - Khorsandi, Javad; Hadaegh, Bahee (Renaissance and Reformation / Renaissance et Réforme, 2023)
The present article explores how William Shakespeare’s King Lear thoughtfully challenges the primacy of sight among the senses, with implications for our understanding of the play’s relationship both to its immediate political context and to the history of ocularcentrism in early modern England. Adopting a new historicist approach, this article claims that writing King Lear in the midst of heated debates on the Anglo-Scottish Union was both a reaction to any possible ocularcentric behaviour by King James and a part of active criticism against the ocularcentrism of the period. Regardless of his personal opinion on James’s plan for the Union, Shakespeare was worried that the king would act according to his ocularcentric understanding of the two countries under his rule. Therefore, King Lear can be read as an advance warning to King James, who needs to be wary of superficial, sight-centred behaviours so as not to suffer the same fate as Lear.